2018
DOI: 10.1016/j.nimb.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Activation cross-sections of proton induced reactions on natHf in the 38–65 MeV energy range: Production of 172Lu and of 169Yb

Abstract: In the frame of a systematical study of light ion induced nuclear reactions on hafnium, activation cross sections for proton induced reactions were investigated. Excitation functions were measured in the 38 -65 MeV energy range for the nat nat Hf(p,x) 169 Yb reactions by using the activation method, combining stacked foil irradiation and off line gamma ray spectroscopy. The experimental results are compared with earlier results in the overlapping energy range, and with the theoretical predictions of the ALICE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13 and the numerical values are collected in Tables 3, 4 and 5. For completeness we have included also the cross section data for production of 172 Hf, measured in present study and reported earlier in [2]. Although all activation products except 177 Lu are formed in reactions on both stable Lu isotopes, remarkable surplus of 175 Lu over 176 Lu (97.4/2.6) results in dominance of the reactions on 175 Lu and in presence of a single peak in the measured excitation functions.…”
Section: Cross Sectionsmentioning
confidence: 86%
See 2 more Smart Citations
“…2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13 and the numerical values are collected in Tables 3, 4 and 5. For completeness we have included also the cross section data for production of 172 Hf, measured in present study and reported earlier in [2]. Although all activation products except 177 Lu are formed in reactions on both stable Lu isotopes, remarkable surplus of 175 Lu over 176 Lu (97.4/2.6) results in dominance of the reactions on 175 Lu and in presence of a single peak in the measured excitation functions.…”
Section: Cross Sectionsmentioning
confidence: 86%
“…We have compared the charged particle production routes for 172 Hf/ 172 Lu generator in our previous paper [2]. Here we reproduce the figure of production yields completed with Lu + d reaction.…”
Section: Hf Productionmentioning
confidence: 99%
See 1 more Smart Citation